Ablation behavior and mechanisms of 3D Cf/ZrB2-SiC composite applied in long-term temperature up to 2400 °C. (September 2021) - Zhang, Dongyang; Yu, Hongying; Wang, Anzhe; Hu, Ping; Ren, Lu; Sun, Dongbai
Highlights: Homogeneous architecture was achieved by vibration-assisted slurry. impregnation combined with precursor impregnation pyrolysis. Long-term ablation behavior and mechanisms of 3D Cf /ZrB2 -SiC composite was studied by oxyacetylene test at 2400 °C. Triple oxide layers of dense ZrO2 and followed by dense SiO2 +ZrO2 and next porous ZrO2 were obtained. The synergy of ZrO2 transportation, coarsening and aggregation increased the stability of the oxide protective layer. Abstract: To evaluate the long-term ablation behavior and mechanism of carbon fiber reinforced ultra-high temperature ceramics, 3D Cf /ZrB2 -SiC composite with homogeneous architecture was prepared via vibration-assisted slurry impregnation combined with precursor infiltration and pyrolysis. The intact structure of sample was remained owing to the triple oxide layers after ablation at Tmax = 2440 °C for 500 s, a dense ZrO2 layer owing to particle accumulation and sintering, followed by a dense SiO2 +ZrO2 layer due to inhibition in diffusion of glassy SiO2 and next porous ZrO2 layer, leading to superior ablation resistance with linear and mass ablation rates of 1.8 × 10 −4 mm/s and 1.08 × 10 -5 g/mm 2 ·s, respectively.